Capsaicinoids, Polyphenols and Antioxidant Activities of Capsicum annuum: Comparative Study of the Effect of Ripening Stage and Cooking Methods - Mansor Hamed; Diganta Kalita; Michael E. Bartolo; Sastry S. Jayanty (MDPI AG, 2019)
Peppers (Capsicum annuum L.) are an important crop usually consumed as food or spices. Peppers contain a wide range of phytochemicals, such as capsaicinoids, phenolics, ascorbic acid, and carotenoids. Capsaicinoids impart the characteristic pungent taste. The study analyzed capsaicinoids and other bioactive compounds in different pepper cultivars at both the mature green and red stages. The effect of roasting on their nutritional content was also investigated. In the cultivars tested, the levels of capsaicin ranged from 0 to 3636 µg/g in the mature green stage and from 0 to 4820 µg/g in the red/yellow stage. The concentration of dihydrocapsaicin ranged from 0 to 2148 µg/g in the mature green stage and from 0 to 2162 µg/g in the red/yellow stage. The levels of capsaicinoid compounds in mature green and red /yellow stages were either reduced or increased after roasting depending on the cultivar. The ranges of total phenolic and total flavonoids compounds were 2096 to 7689, and 204 to 962 µg/g, respectively, in the green and red/yellow mature stage pods. Ascorbic acid levels in the peppers ranged from 223 to 1025 mg/ 100 g Dry Weight (DW). Both raw and roasted peppers possessed strong antioxidant activity as determined by 2,2-diphenyl-1-picrylhydrazyl) reagent (DPPH, 61−87%) and 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS, 73−159 µg/g) assays. Ascorbic acid and antioxidant activity decreased after roasting in the mature green and red stages, whereas total phenolics and flavonoids increased except in the mature green stage of Sweet Delilah and yellow stage of Canrio.